Local integration of African refugees in Egypt; the policy challenges - Soliman, Maha (AUC Knowledge Fountain, 2016)
This research discusses the importance of local integration in dealing with the influx of African refugees in Egypt. Given the obstacles to repatriation, and limited opportunities of resettlement, exploring local integration becomes a necessary alternative. Local integration is generally an overlooked option that given the circumstances can be an applicable course of action for both refugees and host countries. Local integration can potentially provide mutual benefit to both refugees and their host countries. This could be seen in the harnessing of development aid, and can be regarded as a sustainable intervention, that accommodates the local integration of refugees in Egypt. The political will of host governments to support local integration as a long-term solution to refugee populations in their countries is critical. This research explores the concept of local integration within the refugee and asylum seeker community in Egypt. This research will create a framework of analysis of local integration and the policy challenges to achieve that, discuss the resource burdens and other obstacles that prohibit the initiation of policies of local integration, and finally discuss the benefits of local integration.